2014
DOI: 10.1371/journal.pone.0101485
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Ambulatory Medical Care Utilization and Rheumatologist Consultation Predating the Diagnosis of Systemic Lupus Erythematosus: A National Population-Based Study

Abstract: ObjectiveTo investigate the records of ambulatory medical care from patients predating the diagnosis of systemic lupus erythematosus (SLE) using nationwide, population-based claims data.MethodsThe frequencies and costs of ambulatory medical care utilization in 337 newly-diagnosed SLE cases between 2004 and 2010, identified from Taiwan's National Health Insurance Research Database, were compared with 1,348 controls who were frequency matched for sex, age, and the catastrophic illness certificate application yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 37 publications
4
16
0
Order By: Relevance
“…First, the diagnoses of OSA, PD and other comorbidities based on ICD-9-CM might lead to potential misclassification bias. However, the use of ICD-9-CM for patients with chronic diseases has been validated in previous national cohort studies (Chen et al, 2011;Lai et al, 2014;Tsai et al, 2013), and misclassification (if any) was likely to be random and thereby tended to underestimate rather than overestimate the relative risk. Furthermore, the Taiwan NHI samples claims randomly from hospitals, interviews patients and reviews medical charts to verify the accuracy of medical records (National Health Institute, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…First, the diagnoses of OSA, PD and other comorbidities based on ICD-9-CM might lead to potential misclassification bias. However, the use of ICD-9-CM for patients with chronic diseases has been validated in previous national cohort studies (Chen et al, 2011;Lai et al, 2014;Tsai et al, 2013), and misclassification (if any) was likely to be random and thereby tended to underestimate rather than overestimate the relative risk. Furthermore, the Taiwan NHI samples claims randomly from hospitals, interviews patients and reviews medical charts to verify the accuracy of medical records (National Health Institute, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…However, certain limitations are still present in this study. Although SLE is considered to be a severe catastrophic illness in Taiwan, and although patients are registered with the physician’s approval and evaluation by the National Bureau of Insurance, some patients are reluctant to apply for catastrophic care, and these patients may thus be included in the non-SLE cohort 39. However, the size of this population is likely to be insignificant.…”
Section: Discussionmentioning
confidence: 99%
“…In comparison, our study was larger, from a more diverse population and included a control group. A Taiwanese insurance claims study (17) found increased use of medical care in the eight years preceding SLE diagnosis. A shorter time period was used for our study to increase the number of participants with complete data and increase the chance that clinical features were attributable to SLE.…”
Section: Model Validationmentioning
confidence: 99%